VP 2021
DOI: 10.20517/2574-1209.2021.36
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional outcomes after endovascular thrombectomy in patients with and without atrial fibrillation

Abstract: Aim: Patients with atrial fibrillation (AF) are over-represented in endovascular thrombectomy (EVT) populations, due to a high prevalence of large vessel occlusions (LVO) and contraindication to intravenous thrombolysis. This study aimed to: (1) compare 90-day functional outcomes [modified Rankin Score (mRS) 0-2] and mortality in AF vs. non-AF patients receiving EVT; (2) compare 90-day functional outcomes and mortality in AF patients on therapeutic vs. non-therapeutic anticoagulation receiving EVT; and (3) ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Previous studies have reported that AF is significantly associated with worse 90-day outcomes, higher rates of mortality, and comparable rates of successful reperfusion. [14][15][16][17][18][19][20][21][22][23][24] Yet, these previous studies were individually much smaller than the cohort included in our pooled analysis. Interestingly, 1 study 18 included in our analysis could be considered an outlier regarding functional independence rates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that AF is significantly associated with worse 90-day outcomes, higher rates of mortality, and comparable rates of successful reperfusion. [14][15][16][17][18][19][20][21][22][23][24] Yet, these previous studies were individually much smaller than the cohort included in our pooled analysis. Interestingly, 1 study 18 included in our analysis could be considered an outlier regarding functional independence rates.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the included studies ranged from 78 patients to 4169 patients. Eight studies [14][15][16][17][19][20][21]23 included in our analysis were determined to have good quality, while 2 studies 18,22 were determined to have fair quality (eTable in Supplement 1). Patient characteristics, such as age, baseline NIHSS, use of intravenous thrombolytics, and comorbidities, are detailed in the Table.…”
Section: Study Characteristics and Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations